Emotions and Education through the Prism of Feminist Theories - S. V. Volkova (Moscow Polytechnic University, 2019)
The article reflects one of the main trends of the modern philosophy of education - the "affective turn". Drawing upon researches into the history of education as well as feminist theories, the article seeks to understand emotions as means for controlling consciousness, as well as the sphere of socially and culturally constructed experiences that reproduce gender hierarchies. The ambivalent status of a woman in the European educational space is underlined. On the one hand, a woman as a teacher should instill the skills of emotional self-control in students, surrounding them with maternal love. But, on the other hand, a woman was traditionally conceived as a bearer of an irrational principle that puts society and public interests at risk. The author concludes that at the present stage the theme of the relationship between emotions and education has acquired universal significance as a part of a concept of emotional literacy. The ability to empathy and the difficulties of its developing within the framework of emotional literacy training programs are under scrutiny.